STUDENTS’ UNDERSTANDING OF THE REALIZATION OF NOMINALIZATIONS IN SCIENTIFIC TEXT - Fatonah, Fatonah (Universitas Pendidikan Indonesia, 2014)
Abstract: The study reports the investigation of students’ understanding of the realization of nominalizations in scientific text. Nominalization that dominates the language of science is defined as the formation of nouns which come from other nouns (e.g. verbs and adjectives). A strategic question comes up, inquiring about undergraduate students’ level of understanding of nominalizations in scientific text. This study was conducted among 20 Polytechnic students whose study background is engineering. Some numerical data were used, although this study was basically qualitative. The data were not only taken by carrying out an English test, using a scientific reading text, but also by conducting an interview among some of the participants. This test examined their understanding of nominalization, as it is one of the characteristics of scientific text. For analyzing the data, the framework of nominalyzing metaphor was used. This study found that the understanding of nominalizations was at moderate level; that was 65%. It was a bit above the average. It is concluded that this level of understanding nominalizations is not sufficient for the students to comprehend scientific text. Consequently, when reading scientific text, as it was stated in an interview, they experienced some difficulties. This finding is supported by Halliday’s statement that scientific language is difficult to read and to understand. It is recommended that for Polytechnic students some grammatical competence be improved by giving an explicit teaching, particularly with the topic of nominalizations. It is hoped that the higher the students’ understanding of nominalizations, the higher the students’ understanding of scientific text. Keywords: Nominalization, grammatical metaphor, scientific text